2008
DOI: 10.1021/bi801533k
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Studies Indicate That Shigella VirA Is Not a Protease and Does Not Directly Destabilize Microtubules

Abstract: VirA, an essential virulence factor in Shigella disease pathogenesis, is involved in the uptake, motility, and cell-to-cell spread of Shigella organisms within the human host. These functions have been attributed to a VirA protease activity and a mechanism of microtubule destruction via tubulin degradation. We report functional and crystallographic data indicating a novel VirA structure that lacks these activities but highlights the homology to the EspG virulence factor of pathogenic Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 19 publications
(25 reference statements)
3
33
1
Order By: Relevance
“…The structure of an N-terminally truncated VirA, crystallized in a space group different from the full-length protein described here, appeared in press when this manuscript was under review (Germane et al 2008). The results presented here, in particular concerning the novel fold of VirA and the lack of detectable enzymatic activity, are fully consistent with their observations.…”
Section: Note Added In Proofsupporting
confidence: 83%
“…The structure of an N-terminally truncated VirA, crystallized in a space group different from the full-length protein described here, appeared in press when this manuscript was under review (Germane et al 2008). The results presented here, in particular concerning the novel fold of VirA and the lack of detectable enzymatic activity, are fully consistent with their observations.…”
Section: Note Added In Proofsupporting
confidence: 83%
“…MT Disassembly-MT disassembly was assayed essentially as described (12,36,38). Surfaces of double-stick tape flow cells were coated with 1 mg/ml biotinylated BSA followed by 0.1 mg/ml streptavidin.…”
Section: Purification Of His-tagged Proteins-gateway Expression Vectomentioning
confidence: 99%
“…CopN from C. pneumonia was particularly effective at inhibiting MT formation, showing near-complete inhibition at 25 M. Consistent with the observation that CopN binds free ␣␤-tubulin but not MTs, we also observed that it inhibited ␣␤-tubulin polymerization but did not promote depolymerization of MTs. We evaluated the ability of CopN to destabilize MTs by mixing CopN with preformed rhodamine-labeled MT as described (36,38). As shown in Fig.…”
Section: Domain Mapping Experiments Demonstrate That Copn Encodes Thrmentioning
confidence: 99%
“…The Shigella effector VirA also interacts with ␣-and ␤-tubulin heterodimers but induces microtubule destabilization through an ␣-tubulin-specific cysteine protease-like activity (51,52,53). Interestingly, VirA is not a protease, nor does it directly sever or destabilize microtubules (11,15).…”
Section: Vol 78 2010mentioning
confidence: 99%